Pengetahuan Ibu Menyusui Dalam Pemberian ASI Eksklusif - Angelia Friska Tendean (Fakultas Keperawatan, Universitas Klabat, 2019)
ABSTRACT Exclusive breastfeeding is highly recommended for infants aged 0-6 months, where the content of breast milk is in accordance needed by the baby. The research method used descriptive analytic with the cross sectional approach. The purpose of this study was to determine the relationship between knowledge of nursery mothers and exclusive breastfeeding in the working area of ​​the Airmadidi health center. The research sample consisted 34 breastfeeding mothers of infants aged 6-24 months in the working area of the Airmadidi health center. The results obtained were 11 respondents (16.2%) had good knowledge and 11 respondents (16.2%) also had sufficient knowledge, where 21 respondents (61.8%) did not provide exclusive breastfeeding and 13 respondents (38 , 2%) give exclusive breastfeeding. The last education that had good knowledge was D3 / Bachelor 7 respondents (58.3%) and those who gave the most exclusive breastfeeding were high school as many as 9 respondents (56.3%). Based on the number of children who have better knowledge are primipara 8 respondents (53.3%), and those who give the most exclusive breastfeeding are multiparas 7 respondents (41.2%). The results of statistical tests using Pearson Correlation found p = 0.008 <0.05, that meaning there was a significant relationship between the knowledge of nursery mothers and exclusive breastfeeding. The results of statistical tests using Partial Correlation showed that there was a significant relationship between knowledge of breastfeeding mothers and exclusive breastfeeding if the education status and parity factors were included with the value p = 0.018 <0.05 for education status and p = 0.005 <0.05 for parity. Good knowledge will influence the behavior of nursery mothers on exclusive breastfeeding.